The Global Burden of Headache - Saylor, Deanna; Steiner, Timothy J. (Seminars in Neurology, 2018)
At the turn of the century, most of the world's population lived in regions where the prevalence of headache was unknown and its impact poorly understood. Lifting The Burden (LTB), a nonprofit organization in official relations with the World Health Organization, established the Global Campaign against Headache, with the ultimate purpose of reducing the burden of headache worldwide. First, the scope and scale of this burden had to be known. LTB embarked upon a program of population-based studies in countries in all world regions in order to achieve its aim. Its studies have demonstrated a high prevalence of headache disorders, including migraine, tension-type headache, and medication-overuse headache, and their associations with impaired quality of life, substantial lost productivity, and high economic costs in every country surveyed. Informed by these, the Global Burden of Disease study ranks headache disorders as the second leading cause of years lived with disability worldwide; migraine alone is third among people aged 15 to 49 years. With interventions urgently needed to reduce these burdens throughout the world, we review the epidemiological studies conducted by LTB, examine proposed interventions to improve provision of headache care including a three-tier system of structured headache services, and consider the challenges still remaining in providing effective, efficient, and equitable headache care especially in low-income countries.
Keywords: headache; migraine; tension-type headache; medication-overuse headache; burden of disease; intervention; structured headache services; global campaign against headache